The Production of Relatives in Mandarin Children With Specific Language Impairment–From the Perspective of Edge Feature Underspecification Hypothesis - Wang, Haiyan; Yu, Haopeng (Frontiers in Psychology, 2021)
This paper is a first attempt to investigate the production of Relative Clauses (RCs) in Mandarin children with Specific Language Impairment (SLI) (aged 4;5 to 6;0) and their typically developing (TD) controls. The data from a preference choice task suggested that (i) Children with SLI performed better on the subject RC than the object RC, but there was no asymmetry in the production of the two RCs in TDA children; (ii) Children with SLI performed substantially worse than their TD peers on the RCs production; (iii) children with SLI were more inclined to omitting the complementizer and using simple sentences and sentence fragments as avoidance strategies. The Edge Feature Underspecification Hypothesis may explain not only the asymmetry of production seen in children with SLI, but also the presence of errors and avoidance strategies used by this population in the task.